Regulation of Nicotine Biosynthesis by an Endogenous Target Mimicry of MicroRNA in Tobacco. Issue 2 (5th August 2015) - Li, Fangfang; Wang, Weidi; Zhao, Nan; Xiao, Bingguang; Cao, Peijian; Wu, Xingfu; Ye, Chuyu; Shen, Enhui; Qiu, Jie; Zhu, Qian-Hao; Xie, Jiahua; Zhou, Xueping; et al.
Abstract : Endogenous target mimecry of an miRNA affects nicotine biosynthesis. Abstract: The interaction between noncoding endogenous target mimicry (eTM ) and its corresponding microRNA (miRNA ) is a newly discovered regulatory mechanism and plays pivotal roles in various biological processes in plants. Tobacco ( Nicotiana tabacum ) is a model plant for studying secondary metabolite alkaloids, of which nicotine accounts for approximately 90%. In this work, we identified four unique tobacco-specific miRNA s that were predicted to target key genes of the nicotine biosynthesis and catabolism pathways and an eTM, novel tobacco miRNA (nta)-eTMX27, for nta-miRX27 that targets QUINOLINATE PHOSPHORIBOSYLTRANSFERASE2 ( QPT2 ) encoding a quinolinate phosphoribosyltransferase. The expression level of nta-miRX27 was significantly down-regulated, while that of QPT2 and nta-eTMX27 was significantly up-regulated after topping, and consequently, nicotine content increased in the topping-treated plants. The topping-induced down-regulation of nta-miRX27 and up-regulation of QPT2 were only observed in plants with a functional nta-eTMX27 but not in transgenic plants containing an RNA interference construct targeting nta-eTMX27. Our results demonstrated that enhanced nicotine biosynthesis in the topping-treated tobacco plants is achieved by nta-eTMX27-mediated inhibition of the expression and functions of nta-miRX27. To our knowledge, this is the first report about regulation of secondary metabolite biosynthesis by an miRNA -eTM regulatory module in plants.